'Information literacy': Japan's challenge to measure skills beyond subjects. Issue 1 (2nd January 2021) - Shinohara, Masako; Horoiwa, Akira
ABSTRACT: Background : The assessment of cross-curricular skills is gaining attention in many countries. In Japan, the 'Information Literacy Survey for Upper Secondary Students' (the ILSUS) was designed to measure information literacy through Computer-Based Testing (CBT). It was the first large-scale survey based on Item Response Theory (IRT) implemented by Japan's Ministry of Education, Culture, Sports, Science and Technology (MEXT). Purpose : This paper reports on the history and development of the survey and discusses its findings. As 'information literacy' is a generic and cross-curricular ability, we measured cognitive ability relating to how information can be utilised for problem-solving. Main argument : We present some released survey items that were actually used in the ILSUS, to explain how the items covered three aspects of 'information literacy'. Using proficiency levels, we discuss what the findings indicated about the features of the students' 'information literacy': it was evident that, whilst many had the ability to deal with complex and large amounts of information, few were able to address unfamiliar contexts. Then, using questionnaire items from the ILSUS, we report how we determined that 'information literacy' was strongly associated with 'student-teacher relationships' and 'meta-cognition'. Conclusion : This account of the ILSUS offers insight into how we measured information literacy and, more widely, the kinds of skills that Japanese education policy is trying to develop. In planning a new Information Literacy Survey (ILS), we will try to capture what has not been clarified yet, such as the trends in information literacy and differences between educational stages. It may ultimately become possible to specify, more clearly, the goals and teaching methods that should be aimed at in the acquisition and teaching of information literacy.